LCOE Analysis of Tower Concentrating Solar Power Plants Using Different Molten-Salts for Thermal Energy Storage in China - Xiaoru Zhuang; Xinhai Xu; Wenrui Liu; Wenfu Xu (Energies, 2019)
In recent years, the Chinese government has vigorously promoted the development of concentrating solar power (CSP) technology. For the commercialization of CSP technology, economically competitive costs of electricity generation is one of the major obstacles. However, studies of electricity generation cost analysis for CSP systems in China, particularly for the tower systems, are quite limited. This paper conducts an economic analysis by applying a levelized cost of electricity (LCOE) model for 100 MW tower CSP plants in five locations in China with four different molten-salts for thermal energy storage (TES). The results show that it is inappropriate to build a tower CSP plant nearby Shenzhen and Shanghai. The solar salt (NaNO3-KNO3, 60-40 wt.%) has lower LCOE than the other three new molten-salts. In order to calculate the time when the grid parity would be reached, four scenarios for CSP development roadmap proposed by International Energy Agency (IEA) were considered in this study. It was found that the LCOE of tower CSP would reach the grid parity in the years of 2038–2041 in the case of no future penalties for the CO2 emissions. This study can provide support information for the Chinese government to formulate incentive policies for the CSP industry.